2020
DOI: 10.1186/s12891-020-03397-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ligamentous knee injuries in pedestrian versus motor vehicle accidents

Abstract: Background: The purpose of this study was to determine the prevalence and characteristics of ligamentous knee injuries and to compare patient demographics, associated injuries and hospital stay to pedestrians who did not sustain a ligamentous knee injury. Methods: A retrospective review of all adult patients presenting as pedestrians struck by a motor vehicle to a level 1 trauma center over a three-year period was performed. Demographics, length of stay, orthopedic and nonorthopedic traumatic injuries were rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The medial collateral ligament (MCL) injury of the knee joint of pedestrians is common in traffic accidents ( Klinich, 2003 ; Steinmetz et al, 2020 ). MCL injuries cause economic burdens and seriously affect patients’ quality of life ( Chakravarthy et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The medial collateral ligament (MCL) injury of the knee joint of pedestrians is common in traffic accidents ( Klinich, 2003 ; Steinmetz et al, 2020 ). MCL injuries cause economic burdens and seriously affect patients’ quality of life ( Chakravarthy et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have confirmed that pedestrians are injured more severely than any other group of individuals involved in a crash with higher rates of head, pelvic and lower extremity injuries, and a higher mortality rate (22%) compared to vehicle occupants (12%). 4,5 A South Australian study found that the fatality rate of pedestrians was approximately four times higher than that of vehicle occupants. 6 It is recognized that considerable variability exists among individuals in the vulnerability to injuries and death caused by vehicles, with children being particularly susceptible.…”
Section: Introductionmentioning
confidence: 99%